2019
DOI: 10.3390/ijms20071790
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization and In Vitro Biological Properties of Scaffolds Fabricated From Calcium Phosphate Nanoparticles

Abstract: Ceramic materials mimic the mineral composition of native bone and feature osteoconductive properties; they are therefore used to regenerate bone tissue. Much research focuses on increasing the porosity and pore interconnectivity of ceramic scaffolds to increase osteoconductivity, cell migration and cell-cell interaction. We aimed to fabricate biocompatible 3D-scaffolds featuring macro- and microporous calcium phosphates with high pore interconnection. Nanoparticles of hydroxyapatite (HA) and calcium deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 52 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…In this study, the newly synthesized gelatin/nano-hydroxyapatite microspheres (GHM) demonstrated the incorporation of hydroxyapatite into the gelatin fibril which was similar to that of the natural bone (Figure 2B,C) [26]. High HA solid content (40 wt%) in the HA pure scaffolds was reported to be negative for cell viability and proliferation [27]; the ratio between organic and inorganic components (wt% = 37:63) of biomimetic hydroxyapatite microspheres (GHM-S) was similar to that found in natural bone tissue (Figure 2D) [28] and did not show any cytotoxic effect on the hMSCs (Figure 1D).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the newly synthesized gelatin/nano-hydroxyapatite microspheres (GHM) demonstrated the incorporation of hydroxyapatite into the gelatin fibril which was similar to that of the natural bone (Figure 2B,C) [26]. High HA solid content (40 wt%) in the HA pure scaffolds was reported to be negative for cell viability and proliferation [27]; the ratio between organic and inorganic components (wt% = 37:63) of biomimetic hydroxyapatite microspheres (GHM-S) was similar to that found in natural bone tissue (Figure 2D) [28] and did not show any cytotoxic effect on the hMSCs (Figure 1D).…”
Section: Discussionmentioning
confidence: 94%
“…For example, although the size of osteoblasts is in the range of 10–50 μm [ 112 ], regeneration of mineralized bone was enhanced with macropores (100–200 μm) possibly because the lager pore size allows the infiltration of other cells involved in colonization and vascularization [ 113 ]. On the other hand, in contrast to macropores, micropores (pore size <10 μm) provide a greater surface area for cell adhesion and showed better bone protein adsorption [ 114 ].…”
Section: Type Of Msds Targetedmentioning
confidence: 99%
“…Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , termed HAp) composes the primary inorganic contents of human tooth and bone and is a representative of biomineralization and bioinspired materials [34,35,36,37,38,39,40]. Hadagalli et al established mineralization of porous HAp scaffolds, in which pores are obtained using organic pore formers, such as wax, wheat flour, or milk powder, and exhibit good cytocompatibility with osteoblasts in vitro [41].…”
Section: Introductionmentioning
confidence: 99%